Perkembangan Ilmu Hadis di Negeri Terengganu Darul Iman - Baru, Rohaizan (Jurnal Usuluddin, 2006)
This article attempts to find out to what extend have Ilm al- Hadith developed in Terengganu. It highlights the Malay ulamas of Terengganu who contributed to the teaching of ilm al-hadith in the society. It also discusses the non formal studies of ilm al-hadith conducts by ulamas in pondoks as well as the formal studies conducts by scholars in formal learning institutions. However, the research comes to the conclusion that none of the ulamas in the state really specialised in ilm al-ḥadīth and the study in this area is only focused to ilm mukhtalif ḥadīth and ilm ahādīth aḥkām.